Peran Self Criticism sebagai Mediator antara Dating Violence dengan Nonsuicidal Self-Injury - Muliana, Rizki Tri; Rizki, Binta Mu'tiya (Universitas Airlangga, 2025)
Nonsuicidal self-injury (NSSI) is deliberate self-harm without suicidal intent. Dating violence (DV) is a known risk factor for NSSI, but research on this relationship is limited, especially regarding the role of self-criticism (SC). This study examines the role of SC in the relationship between DV and NSSI using a quantitative approach with a correlational design. The participants were 159 early adults aged 18-24 years old. The instruments included the Deliberate Self-Harm Inventory (DSHI) (α=0.9), the Dating Violence Questionnaire-R (DVQ-R) (α=0.901), and Forms of Self-Criticizing/Attacking & Self-Reassuring Scale (α=0.887). This study found that SC acts as a mediator in the relationship between DV and NSSI, β=0.047, (95% CI:0.021; 0.088), z=2.694, p<0.05. These findings suggest that SC may be a key psychological mechanism linking DV to NSSI, highlighting its relevance for preventive and clinical interventions.